THE RECENT CHALLENGED DEVELOPMENT TO IMPLEMENT UNCLOS 1982'S COMMON HERITAGE OF MANKIND - Agustina Merdekawati; Marsudi Triatmodjo; Irkham Afnan Trisandi Hasibuan (Faculty of Law, Universitas Gadjah Mada, 2022)
Abstract The Common Heritage of Mankind (CHM) principle was adopted in UNCLOS 1982 to prevent monopoly of the Area utilization by developed countries. Applying the principle has been challenging and would only get even more challenging during the economic globalization era. There have been rapid changes within the structure of the international community, posing challenges to the implementation of the CHM principle in the area. This paper aims to elaborate on these challenges in the economic globalization era. The research identified that the economic globalization era posed some new and enhanced challenges in applying the principle in the area, questioning its relevance. These challenges are the shifting interests of some developing countries and the increased pressure to obtain more mineral resources to accelerate the conversion to green technologies. The research concluded that the international community is faced with two choices, either to maintain the application of the CHM principle without taking further compromising steps to maximize the goal of achieving the welfare of humanity or re-adjusting the operationalization of the CHM principle in UNCLOS 1982 to adapt to changes in the international community in the era of economic globalization. Abstrak Prinsip Common Heritage of Mankind (CHM) diadopsi dalam UNCLOS 1982 untuk mencegah monopoli pemanfaatan Kawasan Dasar Laut Internasional (Kawasan) oleh negara-negara maju. Penerapan prinsip CHM merupakan sebuah tantangan dan akan menjadi lebih menantang dalam era globalisasi ekonomi. Terdapat perubahan dalam struktur masyarakat internasional, yang akan menimbulkan tantangan bagi penerapan prinsip CHM. Penelitian ini bertujuan untuk menguraikan tantangan- tantangan tersebut di era globalisasi ekonomi. Hasil penelitian menunjukkan bahwa era globalisasi ekonomi memunculkan beberapa tantangan yamg baru dan lebih menantang dalam penerapan prinsip CHM di Kawasan, mempertanyakan relevansinya. Tantangan tersebut adalah pergeseran kepentingan beberapa negara berkembang dan meningkatnya tekanan untuk memperoleh lebih banyak sumber daya mineral guna mempercepat konversi ke teknologi ramah lingkungan. Penelitian menyimpulkan bahwa komunitas internasional menghadapi dua pilihan, yakni antara tetap mempertahankan penerapan prinsip CHM tanpa mengambil kompromi lebih lanjut untuk memaksimalkan potensi manfaat bagi seluruh umat manusia, atau menyesuaikan penerapan prinsip CHM dalam UNCLOS 1982 sebagai respons terhadap perubahan yang terjadi di komunitas internasional dalam era globalisasi ekonomi.